2008
DOI: 10.1021/jp800714s
|View full text |Cite
|
Sign up to set email alerts
|

Topological Properties of Titanate Nanotubes

Abstract: We report a simple ultrasonic-assisted ion-exchange/intercalation process that enables unwrapping onedimensional (1D) titanate nanotubes into two-dimensional (2D) titanate nanosheets. The existence of this 1D to 2D topotactic transformation reveals that the titanate nanotubes could be considered as quasi-2D crystallites with excellent 2D properties such as exfoliation/delamination reactivities although they have the 1D morphology. The resulting titanate nanosheets possess larger band gap energy (∼3.75 eV) than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 46 publications
5
59
0
Order By: Relevance
“…The F KM absorption spectra are shown in figure 3a. As can be seen, a significant red shift in the optical absorption band edge can be observed for the published works [23,24]. Note however that the E g value obtained for the TNT-pH5 sample, 2.81±0.02 eV, is much lower than the E g values of the other two samples, bringing its absorption edge to the near-visible region, in agreement with the above mentioned absorption spectra.…”
Section: Uv-vis Photo-responsesupporting
confidence: 83%
“…The F KM absorption spectra are shown in figure 3a. As can be seen, a significant red shift in the optical absorption band edge can be observed for the published works [23,24]. Note however that the E g value obtained for the TNT-pH5 sample, 2.81±0.02 eV, is much lower than the E g values of the other two samples, bringing its absorption edge to the near-visible region, in agreement with the above mentioned absorption spectra.…”
Section: Uv-vis Photo-responsesupporting
confidence: 83%
“…Due to its favorable physico-chemical properties, it has been widely applied in solar cells, photocatalysts, lithium ion battery electrodes, smart coatings, etc. We refer to the many outstanding reviews already published on such applications for details, and give a brief overview of the most important results below [3,5,29,46,184,[403][404][405][406][407]426,[438][439][440]486]. …”
Section: Applicationsmentioning
confidence: 99%
“…While this is lower than that of other titanates ( $ 3. 4 [46]) it still necessitates UV photons with wavelengths of $ 390 nm or shorter for absorption to occur. In applications such as contaminant removal and disinfection, this may be fine since UV lamps of various geometries, light intensities and spectral windows are commercially available and may be easily installed in reactor setups.…”
Section: Photocatalysismentioning
confidence: 99%
“…Fundamentally, 2-butanol (2-BuOH) represents the simplest chiral alcohol and from a practical standpoint it has been shown to interact enantioselectively with catalytically relevant chiral modifiers. [26][27] For example, temperature programmed desorption (TPD) was used to study L-Proline/Pd and α-(1-Naphthyl)ethylamine (NEA)/Pd surfaces when using R-and S-2-BuOH as probes for surface chirality. [26][27] Interestingly, it was found that on the L-Proline/Pd surface, 2-BuOH was regenerated enantioselectively from 2-butoxide decomposition products and preadsorbed deuterium.…”
Section: Introductionmentioning
confidence: 99%